Design and Synthesis of Novel C2-symmetric bis-cinchona Alkaloid Derivatives - Qin, MingKun; Gao, MingXiang; Li, JiangTao; Jiang, ZhiYong; Yan, Lin (Letters in Organic Chemistry, 2016)
Background: The commercially available dimeric cinchona alkaloids based on C-9 ether bond connecting are limited by the absence of Brønsted acid moiety and cannot meet the enantioselectivity demand. Objective: In this study, a family of novel C2-symmetric bis-cinchona alkaloid derivatives possessing a range of mono- and bidentate hydrogen bond donor groups at the C-9 is now reported. Method: These novel C2-symmetric bis-cinchona alkaloid derivatives were synthesized by a facile route. Results: These novel C2-symmetric bis-cinchona alkaloid derivatives exhibit a rare example of Brønsted acid moiety of C-9, basic tertiary amine moiety, and a rigid enzyme-like pocket, suggesting their potential, broadly useful bifunctional organic catalysts for asymmetric synthesis.
Keywords: Cinchona alkaloids